DEVELOPING FLIPBOOK MULTIMEDIA: THE ACHIEVEMENT OF INFORMAL DEDUCTIVE THINKING LEVEL - Swastika Andini; Budiyono Budiyono; Laila Fitriana (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
The geometry in flipbook multimedia can improve the necessary skills of the 6th graders, so that achieve the highest level of geometric thinking that is informal deductive. The flipbook which uses technology with flipping experience, animation, video, and music is different than the ordinary printed book. Also, it looks more exciting and interactive for students. The aim of this research measures flipbook effectiveness on limited-scale and wide-scale tryout, it is reviewed from Skill Gist Competence domain (KI-4) of Curriculum 2013 on geometry primary skill indicator, also examining flipbook efficacy if it is compared with the printed book which has been used before. The instrument used on a limited-scale tryout and wide-scale tryout is a rubric assessment of product-based and performance-based. However, the tool used on the efficacy test is an achievement test which consists of twenty questions of multiple choice. The test material in the achievement test is about quadrilateral and problem-solving. Based on statistic analysis result on the efficacy test, the research result shows that student’s capability who uses flipbook is better than the student who doesn’t, in learning geometry. Furthermore, the conclusion is that flipbook multimedia is more efficacy than before product.